How do we identify RHD variants using a practical molecular approach?. Issue 4 (28th February 2014) - Arnoni, Carine Prisco; Latini, Flavia Roche Moreira; Muniz, Janaína Guilhem; Gazito, Diana; Person, Rosangela de Medeiros; de Paula Vendrame, Tatiane Aparecida; Barreto, José Augusto; Castilho, Lilian
<x xml:space="preserve">Abstract</x> Serologic resolution of Rh discrepancies due to partial D or weak D phenotypes is a frequent problem encountered during routine typing that can be solved by RHD genotyping because it provides better characterization of these variants. The objective of the current study was to develop algorithms for identification of D variants in multiethnic populations based on a logic sequence of molecular tests using a large number of atypical RhD specimens. Thus, a total of 360 blood samples with atypical D antigen expression were analyzed. A previously published multiplex polymerase chain reaction (PCR) procedure was performed and depending on multiplex PCR analysis, the associated RHCE allele, and D variant frequency in our population, an algorithm was developed composed of six flow charts using specific PCR–restriction fragment length polymorphism and/or specific exon sequencing. This strategy allowed the identification of 22 different variants with few assays and a much reduced cost. This study describes a simple and practical algorithm that we use to determine RHD genotypes in samples with unknown RHD. This strategy is relatively easy to implement and the algorithm can be adapted to populations with various ethnic backgrounds after an initial assessment of the type and frequency of D variants. Essentially, we demonstrate that sequencing of all RHD exons is not necessary for the identification of the majority of known D variants.